2016
DOI: 10.1007/s00784-016-1902-4
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of five intraoral scanners compared to indirect digitalization

Abstract: Regarding the accuracy, all tested intraoral scanning technologies seem to be able to reproduce a single quadrant within clinical acceptable accuracy. However, differences were detected between the tested systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
144
1
11

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 169 publications
(158 citation statements)
references
References 15 publications
2
144
1
11
Order By: Relevance
“…The precision of the digital model was determined by the accuracy of the scanner. For the accuracy analysis of the digital model, a previously introduced method was utilized (Mitsopoulou et al, ; Guth et al, ). The results indicated that most deviations within the digital models were small.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precision of the digital model was determined by the accuracy of the scanner. For the accuracy analysis of the digital model, a previously introduced method was utilized (Mitsopoulou et al, ; Guth et al, ). The results indicated that most deviations within the digital models were small.…”
Section: Discussionmentioning
confidence: 99%
“…Using the “deviation analyzing” function, the three‐dimensional Euclidean distances (EDs) for point clouds were calculated, using positive or negative values in relation to the reference dataset. Deviations between the test and reference datasets were given as the following parameters: positive deviation, negative deviation, average deviation, and standard deviation (Guth et al, ). Geomagic thereafter exported an analysis report displayed in a color‐map deviation spectrum to indicate differences in overall surface geometry.…”
Section: Methodsmentioning
confidence: 99%
“…Intraoral scanners were first introduced more than 30 years ago (Duret & Preston, ). Since then, continuous steps have been taken towards their development and nowadays, with the improvements implemented by new devices and software (Mangano, Gandolfi, Luongo, & Logozzo, ), together with social acceptance of these new technologies, conventional impressions are being replaced by digital ones (Güth, Keul, Stimmelmayr, Beuer, & Edelhoff, ; Güth et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Today, engineering technologies such as computer‐aided design/computer‐assisted manufacture have advanced at high speed in dental medicine . These methods require the use of stereolithography (STL) files which can be acquired with an intraoral scanner (IOS), or extraorally using a stone cast poured from a conventional impression and digitalized via laboratory scanner …”
Section: Introductionmentioning
confidence: 99%
“…8,10,11 These methods require the use of stereolithography (STL) files which can be acquired with an intraoral scanner (IOS), 12,13 or extraorally using a stone cast poured from a conventional impression and digitalized via laboratory scanner. 14…”
mentioning
confidence: 99%